Analysis of the legal attributes and implications of professional dental assistants: view of the assistant him - Marco Antonio Scanavini; Danilo Furquim Siqueira; Ivan Delgado Ricci; Silvana Tomasso; Luiz Renato Paranhos (Faculdade São Leopoldo Mandic, 2009)
Objective: To analyze the attributes and legal implications of the Dentists' Assistants, both from the aspect of the use of their services and their education/training. Methods: Five hundred questionnaires were distributed to Dentists' assistants in private clinics in the region of Piracicaba, São Paulo, of which 127 (25.4%) returns were received, answered by the assistants themselves.Results: All the professionals researched were women, and 55.9% of them had completed high school. The majority of the assistants were trained by the dentist him/herself, sometimes exceeding, and at other times falling short of the demands of their functions. The majority (18.1%) were registered with the Regional Council of Dentistry and 74.8% were registered in the Employment Books. No assistants were sued by or received warning from the Regional Council of Dentistry.Conclusion: Wider publication of the Dental Code of Ethics and consolidation of norms for procedures in the Dentistry councils as regards professionals and assistants is important in order to avoid misuse of their services. Stricter monitoring is required to prevent assistants from performing inadequate activities, as well as those outside of their professional education.